Visual Perceptions - A. Tzavaras (Law Text Culture, 2008)
The most perplexing aspect of the ‘war through terror’ or the ‘war against terror’ is the imperceptibility of the enemy, the lack of a defined combat zone and a clear-cut border between ‘them’ and ‘us’ that creates a social anxiety interface in the interactive multicultural nature of the Australian ethos. The notion of terror as a strategy with the aim of affecting public opinion is aided by popular media, the nefarious images that metamorphose into the privacy of our home: scenes of torture, brutality and death, acts of willful profanity that undermine basic human and moral principles.